2018
DOI: 10.1002/2017gb005698
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Mineralization of Terrigenous DOC to Dissolved Inorganic Carbon in Ocean

Abstract: When terrigenous dissolved organic carbon (tDOC) rich in chromophoric dissolved organic matter (tCDOM) enters the ocean, solar radiation mineralizes it partially into dissolved inorganic carbon (DIC). This study addresses the amount and the rates of DIC photoproduction from tDOC and the area of ocean required to photomineralize tDOC. We collected water samples from 10 major rivers, mixed them with artificial seawater, and irradiated them with simulated solar radiation to measure DIC photoproduction and the pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
68
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(80 citation statements)
references
References 92 publications
(344 reference statements)
10
68
2
Order By: Relevance
“…) indicating that the marine end‐member is the important FDOM source rather than the local runoff. The reduced intensity of visible wavelength FDOM in the freshwater influenced surface layer could potentially also have been caused by photochemical degradation (Ward et al ; Aarnos et al ). However, as the ice in the Young Sound fjord system disappears after the summer solstice, the sun angle is also decreasing rapidly and as a result, the inner fjord system is shaded by surrounding mountains preventing direct exposure.…”
Section: Discussionmentioning
confidence: 99%
“…) indicating that the marine end‐member is the important FDOM source rather than the local runoff. The reduced intensity of visible wavelength FDOM in the freshwater influenced surface layer could potentially also have been caused by photochemical degradation (Ward et al ; Aarnos et al ). However, as the ice in the Young Sound fjord system disappears after the summer solstice, the sun angle is also decreasing rapidly and as a result, the inner fjord system is shaded by surrounding mountains preventing direct exposure.…”
Section: Discussionmentioning
confidence: 99%
“…However, our knowledge of the biogeochemical cycling of peat-derived DOM in Southeast Asia is still limited. Although several studies have shown that peatland-draining blackwater rivers in Sumatra and Borneo carry extremely high DOC concentrations (3000-5500 µmol L −1 , or 36-66 mg L −1 ) with a predominantly terrestrial origin (Alkhatib et al, 2007;Baum et al, 2007;Rixen et al, 2008;Harun et al, 2015Harun et al, , 2016Müller et al, 2015Müller et al, , 2016Cook et al, 2017), more detailed analysis of the chemical composition of peat-derived DOM, and determination of its lability to different degradation processes, are mostly lacking. Moreover, most of these studies did not sample beyond the upper estuaries.…”
Section: Introductionmentioning
confidence: 99%
“…Hereby, wetlands play a remarkable role in controlling carbon sequestration (Aiken & Cotsaris, 1995;Cook et al, 2017;Dittmar et al, 2006;Moyer et al, 2015) from inland sources. Overall, half of the carbon exported from inland waters reaches the oceans as organic molecules (Aarnos et al, 2018;Battin et al, 2009). Therefore, quantification of riverine carbon fluxes from dynamic tropical forests may contribute to (a) validate global predictions and (b) reduce uncertainties of carbon sequestration estimates under different climate change scenarios (Shih et al, 2018;Tranvik et al, 2018).…”
Section: Introductionmentioning
confidence: 99%